Resistência de Rhipicephalus microplus a associações comerciais de organofosforados e piretroides sintéticos no estado do Rio Grande do Sul, Brasil - Reginato, Caroline Zamperete (2016)
Rhiphicephalus microplus is one of the main ectoparasites of cattle in regions of tropical and subtropical climate. The economic losses caused by this parasite are related to treatment costs, decreased productivity and disease transmission. Currently the use of chemical products is still the most common form of control of the cattle tick, however, its use in an inadequate and suppressive way, has been causing the development of resistance to different classes of commercially available acaricides. Thus, the control of this parasite has been characterized by presenting a great challenge for technicians and producers. An alternative to tick control is the association of two different pharmacological bases, and currently this form of presentation is widely found commercially. The objective of this work is to describe the evaluation of the effectiveness of organophosphates and synthetic pyrethroids based on different combinations of R. microplus in the state of Rio Grande do Sul, Brazil. For this, 54 samples of cattle farms were collected, located in different municipalities of the state of Rio Grande do Sul. The evaluation of the in vitro efficacy of the acaricides tested was performed through the adult immersion test (AIT). In order to carry out the tests, four commercially available products were chosen: Ectoparasiticide A - 15% cypermethrin + 25% chlorpyrifos + 1% citronellal - (Colosso®, Ouro Fino Animal Health), Ectoparasiticide B - 15% cypermethrin + 30% chlorpyrifos + 15% fenthion - (Colosso FC30®, Ouro Fino Animal Health), Ectoparasiticide C - 50% chlorpyriphos + 6% cypermethrin high-cis - (Flytion®, Clarion Biosciences Ltda.) and Ectoparasiticide D - 16% ethion + 8.5% chlorpyriphos + 5% alpha-cypermethrin - (Potenty®, MSD Animal Health). The cypermethrin/ chlorpyrifos/ fenthion combination showed the best results, with an average efficiency greater than 95%, being effective in 94.44% (51/54) of the tested farms. The product containing the cypermethrin / chlorpyrifos / citronellal combination had a lower mean efficacy (62.11%), being effective in only 29.62% (16/54) of the properties tested. R. microplus presents different degrees of resistance to the association of organophosphates and synthetic pyrethroids, and multiple resistance was observed in most of the populations studied. Only the cypermethrin/ chlorpyrifos/ fenthion combination showed acceptable mean levels of efficacy in the tick populations studied. In this way, it is essential to establish a frequent monitoring of the effectiveness of the carrapaticides used, in order to prolong their useful life, contributing to their rational use for tick control in cattle.